Genetic and physiological tests of three phosphate-specific transport mutants of Escherichia coli. - Zuckier, G (1981)
Phosphate-specific transport system mutations phoT35, pst-2, and phoS25-(Am) were mapped between bgl and glmS, at about 83 min on the Escherichia coli chromosome. All three mutations were recessive to wild-type genes on transducing bacteriophage lambda asn. The phoS25 (Am) and pst-2 mutations were also recessive to transducing phage lambda dglm; however, the phoT35 mutation was not. This suggests that phoT35 lies in a different complementation group from phoS25 (Am) or pst-2. Isogenic series of strains carrying these mutations were constructed in two genetic backgrounds, pit+ (wild type) and pit (relying entirely on the phosphate-specific transport system for phosphate uptake). The pst-2 pit double mutant was incapable of Pi utilization, but the phoT35 pit double mutant exhibited no such deficiency.